Social thinking, ecology and bioethics - Ortega Cabrera, Agustín (2019)
This work presents the teaching of the faith of the Catholic Church as presented by the Popes, like Francisco, on social and moral thinking, with his teaching on integral ecology, which is a global bioethics in the defense of life and dignity of the Church. person in all its phases, shapes and dimensions. A message that promotes personal, social and ecological justice with a human and global development.